Near nerve potencial of sural nerve in leprosy - Ana Paula M. Arruda; Wilson Marques Jr; Norma T. Foss; José A. Garbino; Marcos Virmond; Amilton A. Barreira (Arquivos de Neuro-Psiquiatria)
Leprosy neuropathy is characterized by initial involvement of the small nerve fibers, later followed by involvement of the large fibers, when routine nerve conduction studies become abnormal. To increase the diagnostic yield and precocity of these studies, we applied the near nerve technique to the sural nerve of 8 leprosy patients. Contrary to our expectations, the main component of the sural nerve sensory action potential was abnormal in all patients, but the minimum conduction velocity originating from small 3-6 mm fibers was normal or only mildly involved in three patients. Also, although Schwann cells are the first to be involved in leprosy, the results are suggestive of axonal degeneration instead of demyelination. To better understand the neurophysiology and physiology of leprosy and to increase the accuracy and precocity of the diagnosis, it will be necessary to investigate patients in the very early stages of the disease and to correlate these findings with the corresponding nerve pathology.